Sociocultural Representation in the Use of Speech Acts - Sutikno, Bellatrix Angelicamila; Setyorini, Ajeng; Hidayat, Nur (Universitas Pahlawan Tuanku Tambusai, 2024)
This research explores analyse the word speech action by socio-cultural approach that values frequently found in the novel